Nonlinear Dynamics and Applications - José M. Amigó; Fernando Montani (Entropy)
Nonlinear dynamics is the study of dynamical systems in finite dimensions, whether in discrete or continuous time, in which the evolution equation (a difference or differential equation, respectively) is not linear in the state variables [...]